Guided tissue remineralization and its effect on promoting dentin bonding - Yao, Wei; Ma, Liang; Chen, Ruhua; Xie, Yimeng; Li, Bing; Zhao, Bin (Frontiers in Materials, 2022)
With the deepening of research on condensed matter chemistry, artificially guided demineralized dentin remineralization has changed from a classical remineralization pathway of the thermodynamic deposition mode to a biomimetic mineralization mode. This new mode is more consistent with the biological mineralization process. The biomimetic mineralization model can successfully simulate natural mineralization and restore the microstructure and mechanical properties of demineralized dentin. Therefore, it has a good application value in the treatment of caries and dentin hypersensitivity and adhesive restorations. This paper analyzes the principles of guided tissue remineralization and describes new research findings related to the classical mineralization model and the novel biomaterials developed using the biomimetic mineralization mode in detail. It also describes the application of these principles to improve the dentin bonding system. It thus shares the new findings in guided tissue remineralization applied to dentin bonding systems. Finally, the existing problems in this field and future development directions are proposed.